1967
DOI: 10.1192/bjp.113.501.895
|View full text |Cite
|
Sign up to set email alerts
|

A Manic Depressive Psychotic with a Persistent Forty-eight Hour Cycle

Abstract: Richter (1960) reviewing knowledge about biological “clocks” in medicine and psychiatry, emphasized the incidence of 48-hour cycles of physical and mental symptoms. He considers that the mental symptoms are not specific and can be manic depressive or schizophrenic. Menninger-Lerchenthal (1960), in his book on periodicity in psychopathology, devoted a section to 48-hour rhythms and lists references to 48-hour cycles in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
2

Year Published

1969
1969
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(17 citation statements)
references
References 32 publications
2
13
0
2
Order By: Relevance
“…1,9,10 More recent studies have confirmed these earlier observations in small samples of well diagnosed BPD patients using systematic prospective study designs with well-validated rating instruments administered at 2-h intervals. 8,25 These studies indicate that a distinct pattern of UURC or ultradian cycling can be reliably distinguished from classical rapid-cycling affective episodes (months to weeks).…”
supporting
confidence: 65%
“…1,9,10 More recent studies have confirmed these earlier observations in small samples of well diagnosed BPD patients using systematic prospective study designs with well-validated rating instruments administered at 2-h intervals. 8,25 These studies indicate that a distinct pattern of UURC or ultradian cycling can be reliably distinguished from classical rapid-cycling affective episodes (months to weeks).…”
supporting
confidence: 65%
“…The mood changes, which had been experienced over several years by the patient, occurred with clockwise regularity similarly to cases described earlier Jenner et al, 1967;Doerr et al, 1979;King et al, 1979;Gann et al, 1993;Kramlinger and Post, 1996]. As in other cases with 48-hour rapid cycling, the disorder began without a preceding history of bipolar or any other affective disorder.…”
Section: Discussionsupporting
confidence: 51%
“…Both high-and low frequency cycles have been reported in other studies for various species, including primates. Ultradian cycles have been observed in human (Schaefer et al, 1967) and in monkeys (Winget et al, 1968); and infradian cycles have been reported for humans (Halberg, 1965;Jenner et al, 1967Jenner et al, , 1968, and suggested for monkeys (Richter, 1968). More research is needed before the significance and validity of such cycles can be determined.…”
mentioning
confidence: 91%